(untitled) - D F Shriver (Oxford, New York, 1994)
This book is divided into three parts: *) Part 1 (Foundations) covers atomic structure and molecular and solid state structure and bonding. Acid-base interactions, metal complexex, and oxidation-reduction reactions also appear i Part i. *) Part 2 (Systematic chemistry of the elements) opens with a new chapter on the chemistry of the metals. *) Part 3 (Advanced topics) covers bonding, spectra, and reactions of d-block complexes, and d-block organometallic compounds, catalysis, and bioinorganic chemistry
Anh văn chuyên môn - Hóa học
Keywords: chemistry, inorganic